Cuckoo search as a tool for optimal design of PM brushless DC motor - Cvetkovski Goga, Petkovska Lidija and Lefley Paul (Emerald Publishing Limited, 2018)
The purpose of this paper is to perform an optimal design of a single-phase permanent magnet brushless DC motor (SPBLDCM) by using efficiency of the motor as an objective function. In the design procedure of the motor, a cuckoo search (CS) algorithm is used as an optimization tool.For the purpose of this research work, a computer program for optimal design of electrical machines based on the CS optimization has been developed. Based on the design characteristics of SPBLDCM, some of the motor parameters are chosen to be constant and others variable. A comparative analysis of the initial motor model and the CS model based on the value of the objective function, as well as the values of the optimization parameters, is performed and presented.
Keywords: Design optimisation, Finite element analysis, Permanent magnet machine, Electric motors, Optimal design, Cuckoo search